VERSIONS OF ASSOCIATIVE COMMUNICATION IN O. MATJON’S POEMS - Rahmonov Husanboy Abjalil ogli (Galaxy International Interdisciplinary Research Journal, 2022)
This article is devoted to analysis Omon Matjon’s poems. Association units have been selected and discussed deeply in the article.